Fetomaternal Effects of Obesity in Postdate and Induced Pregnancies - NoureenYousaf , Kinza Alam , Aisha Yousaf , Tahir Ahmad Munir , Inaam Qadir J.Hashmi , Haider Ali, NoureenYousaf , Kinza Alam , Aisha Yousaf , Tahir Ahmad Munir , Inaam Qadir J.Hashmi , Haider Ali (Journal of Rawalpindi Medical College, 2017)
Background : To study the fetomaternal effects of obesity in post date and induced pregnancies. Methods: In this case control study 210 postdate patients were included. They were divided into obese and non-obese groups according to BMI. Patient’s age, parity, and duration of gestation was recorded. Induction was done, mode of delivery, PPH, perinatal outcome i.e. macrosomia, birth outcome, and shoulder dystocia was noted. Results;The mean age was 23.05±3.61 years. All patients were postdate and underwent induction. BMI showed an increase with increase in age.Fifty seven percent of obese compared to 32% of non-obese needed low segment caesarean section (LCSC). Shoulder dystocia occurred in 2% of obese and 1% in non-obese while PPH occurred in 23% and 9.6% in obese and non-obese females respectively. Macrocosmia was encountered in 25% of obese versus 5% non-obese while stillbirth was observed in 3% of obese group. Clavicle fracture 1% was noticed only in obese females. Conclusion: Maternal obesity is associated with adverse maternal and fetal outcomes in pregnancy including operative deliveries, PPH with fetal macrosomia, birth anoxia, and stillbirth. So these women should be treated as high risk pregnancies